Edge control approach based on image processing in paper and packaging production - Altundogan, Goktug; Karakose, Mehmet; Sarimaden, Alisan; Akin, Erhan (Institute of Electrical and Electronics Engineers Inc., 2017)
Minimizing the losses that will occur in the production phase is a very important issue in industry. Many digital and electronic solutions are being used in the industry in order to prevent situations that may cause loss. If these solutions are dealt with in two steps, the first step is to determine the likely cause of the possible loss. The second step is to prevent problems by eliminating the fault in the determined case. Particularly in the packaging sector and the paper sector, slip and position changes that may occur during the flow through the conveyor belt before the raw mine is processed cause defects on the product. For this reason, it is very important for the industrial applications mentioned to be able to detect a possible slip situation and to be able to intervene quickly in order to eliminate this slip to avoid any malfunction. Highly efficient results can be achieved with image processing techniques to detect situations such as slippage of raw material flowing through the conveyor belt. In this study, an approach has been made to detect the amount of slip accurately using image processing based edge detection algorithms and to intervene with the help of stepper motors. The developed system in this study has been tested on different colored surfaces according to the sensitivity of the detection algorithm and the response speed of stepper motors. The developed image processing algorithm in this paper is implemented on an ARM based development card. The algorithm produces output according to the direction of the possible slip and applies force in the direction of the stepping motor slip due to the divided threads. Synchronization of processes in this study through threads has increased the reaction speed of stepper motors. The efficiency of detecting the amount of slippage of the algorithm developed in experimental data and the response speed of the stepper motor according to this proved itself. © 2017 IEEE.
2017 International Artificial Intelligence and Data Processing Symposium, IDAP 2017 -- 16 September 2017 through 17 September 2017 -- Malatya -- 115012
Keywords: Edge control; Image processing; Packaging production